2018
DOI: 10.1001/jama.2018.14433
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Performance of Common Measures of Weight Regain After Bariatric Surgery for Association With Clinical Outcomes

Abstract: IMPORTANCE Estimates of weight regain following bariatric surgery vary widely. OBJECTIVE Describe weight regain following post-Roux-en-Y gastric bypass (RYGB) weight nadir, and compare common weight regain measures for association with clinical outcomes. SETTING Ten hospitals in six US cities: Portland, OR, Seattle, WA, Fargo, ND, Pittsburgh, PA, New York, NY and Greenville, NC. DESIGN AND PARTICIPANTS Adults undergoing bariatric surgical procedures entered a prospective cohort study between February 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
235
2
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(267 citation statements)
references
References 46 publications
15
235
2
15
Order By: Relevance
“…However, in the long-term, these results are not maintained in all patients. There is growing recognition that weight regain is a concern after bariatric surgery [3][4][5][6][7][8]. Weight regain has been associated with deterioration in HRQoL, the reemergence of type 2 diabetes and other comorbidities, and patients' opinion about surgery success [3,4,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the long-term, these results are not maintained in all patients. There is growing recognition that weight regain is a concern after bariatric surgery [3][4][5][6][7][8]. Weight regain has been associated with deterioration in HRQoL, the reemergence of type 2 diabetes and other comorbidities, and patients' opinion about surgery success [3,4,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of the percentage of patients who regain a significant amount of weight vary widely [4][5][6][7][8]. In a systematic review among 16 studies, weight regain rates ranged from 19 to 87% for patients who underwent RYGB and sleeve gastrectomy (SG), while a systematic review among 21 studies found weight regain rates after SG ranged from 6 to 76% over variable follow-up periods ranging from 2 to 6 years [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight development from baseline through 5 years was reported by standard measures: percentage excess weight loss (%EWL), percentage excess BMI loss (%EBMIL), percentage total weight loss (%TWL) and change in BMI. Weight regain, from nadir weight occurring between 1 and 2 years after surgery to 5 years, was reported as change in BMI and percentage of maximum weight loss.…”
Section: Methodsmentioning
confidence: 99%
“…Dyslipidaemia was based on the presence of fasting LDLc ≥ 160 mg/dL, HDLc ≤ 40 mg/dL, fasting triglyceride ≥ 200 mg/dL or active use of lipid lowering therapy [19]. Weight regain was calculated as the difference between the weight lost at nadir and the weight on the last observation expressed as percentage [20].…”
Section: Diagnostic Criteria To Define Metabolic and Weight Responsesmentioning
confidence: 99%